Nutritional and biochemical profile and bioactive properties of four Greek local landraces of onion - Polyzos, Nikolaos; Almeida, Daiana; Fernandes, Ângela; Pires, Tânia S. P.; da Silveira, Tayse F. F; Barros, Lillian; Petropoulos, Spyridon A. (Frontiers in Plant Science, 2026)
IntroductionThe preservation of genetic diversity of horticultural crops is essential for modern agroecosystems that face pressure from climate change and the intensification of crop production.MethodologyIn the present work, the nutritive value, chemical profile and bioactive properties of four Greek onion local landraces were investigated for the first time. The tested genotypes included three local landraces originated from the region of Thiva, one landrace collected from Evoia, as well as one commercial cultivar which was used as the control treatment. All the genotypes were assessed in terms of nutritional value, chemical composition and bioactivities.Results and discussionOur results indicate a high variability in the nutritive value and the chemical profile of the studied genotypes, while varied bioactive properties were also recorded. The bulbs of the local landrace ON5 were the richest in polyphenols and quercetin in particular, a finding which was also accompanied by the highest antioxidant activity. On the other hand, the commercial cultivar was the richest in total and individual free sugars, as well as in total dietary fibers and total organic acids, results which indicate a sweeter taste and higher pungency. In conclusion, the studied landraces showed promising properties and they could be further valorized through the implementation of breeding programs aiming to produce new elite onion genotypes with high nutritional and bioactive potential.